The Impact of Early-Life Exposure to Air-borne Environmental Insults on the Function of the Airway Epithelium in Asthma - Kirsten Spann; Natale Snape; Engin Baturcam; Emmanuelle Fantino (Ubiquity Press, 2016)
The airway epithelium is both a physical barrier protecting the airways from environmental insults and a significant component of the innate immune response. There is growing evidence that exposure of the airway epithelium to environmental insults in early life may lead to permanent changes in structure and function that underlie the development of asthma. Here we review the current published evidence concerning the link between asthma and epithelial damage within the airways and identify gaps in knowledge for future studies.